ASSESSMENT OF SUSCEPTIBILITY TO SΕA-LΕVEL RISE IN THE COASTAL AREA OF PIERIA PREFECTURE - Mavromatidi, A.; Karymbalis, E. (Bulletin of the Geological Society of Greece, 2016)
Tourism development in Greece has led to increasing pressure on coastal areas, which makes the study of sensitive coastal areas essential, in order to find appropriate solutions for their shielding. The aim of this study is an estimation of the effects of an anticipated sea level rise for the touristically developed part of Pieria Prefecture, which includes the settlements Paralia, Skala of Katerini, Olympic Beach, Korinos Beach and extends north to the area of the Kitrous saltworks and south to the mouth of Mavroneri river. Therefore the Coastal Vulnerability Index (CVI) is applied, in an attempt to determine the susceptible parts to the potential sea level rise. CVI depends on the following parameters: (a) coastal geomorphology, (b) coastal slope, (c) shoreline erosion/accretion rate, (d) relative sea-level rise fluctuations, (e) mean tidal range and (f) mean significant wave height. The classification of the coast, which is of particular socio-economic significance since it hosts urbanized areas, into five CVI classes (from very low vulnerability to very high vulnerability), showed that 43.6% of the entire coastline is of very high vulnerability.